EFFECT OF CUSTOMERS’ DEMOGRAPHICS ON RETAIL FORMAT CHOICE AND INTERACTION: A STUDY ON RETAIL SECTOR IN INDIA - Kumar, Pankaj (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of the study is to examine how often customers interact with different types of retail formats. A structured questionnaire was successfully distributed to 600 respondents, who had made purchases from sixty retail formats operated in Delhi and Gurugram belonging to the domain of Shopping Malls, Hypermarket, Supermarket, Department Stores, Discount stores and Category Killers through systematic stratified sampling for the collection of data. To segment the customer groups for each of the four retail formats (shopping mall, supermarket, department store, and category killer) based on demographic variables (gender, age, marital status, occupation, and income), a two-way ANOVA was used on the shopping frequency of the respondents. The Chi-square (χ2) test was also used to test the significant differences in shopping motives, companion during their visit, whether a planned or unplanned shopping trip, the staying time in a retail format of the respondents based on their gender and age. The study found that gender and age, gender and occupation, and gender and education are more or less equally important factors, whereas gender and marital status, and gender and income were not found important factors in affecting store visits. The study also found the behavioral aspect of retail customers in many ways. First, their visits to the stores were primarily driven by purchase needs, either window shopping or making actual purchases followed by eating. Second, more people prefer to visit these stores along with their friends or family; this result contributes to that being accompanied by others (Companion), shoppers more likely to buy food and less likely to buy non-food products.